Crip theory and the disabled identity: why disability politics needs impairment - Jenks, Andrew (Disability & Society, 2019)
This article highlights the importance of recognizing both the ontology of impairment as it relates to the creation of the disabled identity as well as why articulations of the disabled identity being ‘crip’ obfuscate potential politics. Examining how the disabled identity has been cast as a coherent social and political category, rather than the messy and complicated identity it truly is, I argue the adoption of a post-structuralist orientation by activists and advocates is bad for disability politics. Providing two examples, the first focusing on a publicized rape case of a person with an intellectual disability and the second on the importance of disability rights claims based on visibility of impairment, I show how articulations like those made in crip theory can have serious, negative implications for the lived experience of people with disabilities. I conclude with a call for disability studies scholars to engage disability politics in their work.
Keywords: 2000 à aujourd'hui; 2010-2019; activisme; approches et analyses; capacitisme; care; corps; cours; crip; discipline; droit; droit des personnes en situation de handicap; histoire et politique; justice sociale; postmodernisme; premier cycle; périodes historiques; ressource en ligne; santé; science politique; science politique et droit; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

Displaying Families - Finch, Janet (Sociology, 2007)
This article argues that the sociology of contemporary family relationships should be developed to recognize the importance of ‘displaying’ as well as ‘doing’ family. The addition of the concept of ‘display’ to the sociological tool kit is not only a necessary complement to the important conceptual developments which have taken place in recent years, but is also rich in its potential for further empirical and theoretical work. In developing this theme, the article examines empirical evidence from recent UK studies of family relationships, exploring why ‘display’ is important in contemporary family relationships as well as the process through which it occurs. The article represents an initial exploration of these themes. The author's principal aim is to open up this aspect of family life for debate within the relevant sociological research community, encouraging others to refine the concept as well as to use it.
Keywords: 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; care; cours; discipline; europe; famille; hétérosexualité; maternité; postmodernisme; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; thématiques